Role of PI3-Kinase in Angiotensin II-Induced Cardiac Hypertrophy: Class I Versus Class III - Zhong, Tiecheng; Wang, Zonggui; Niloy, Sayeman Islam; Shen, Yue; O’Rourke, Stephen T.; Sun, Chengwen (Frontiers in Pharmacology, 2021)
Cardiac hypertrophy is initially adaptive to hemodynamic overload; however, chronically it contributes to heart failure and sudden cardiac death. The extracellular regulatory factors and intracellular signaling pathways involved in cardiac hypertrophy are not fully clear. The aim of current study was to examine the role of PI3-kinases Class I (PI3KC1) and Class III (PI3KC3) in angiotensin (Ang) II-induced cardiac hypertrophy. The results demonstrate that treatment of cardiomyocytes with Ang II caused dose-dependent increases in autophagy, with an increasing phase followed by a decreasing phase. Ang II-induced autophagic increases were potentiated by inhibition of PI3KC1 with LY294002, but were impaired by inhibition of PI3KC3 with 3-methyladenine (3-MA). In addition, blockade of PI3KC1 significantly attenuated Ang II-induced ROS production and cardiomyocyte hypertrophy. In contrast, blockade of PI3KC3 potentiated Ang II-induced ROS production and cardiac hypertrophy. Moreover, blockade of PI3KC1 by overexpression of dominant negative p85 subunit of PI3KC1 significantly attenuated Ang II-induced cardiac hypertrophy in normotensive rats. Taken together, these results demonstrate that both PI3KC1 and PI3KC3 are involved in Ang II-induced cardiac hypertrophy by different mechanisms. Activation of PI3KC1 impairs autophagy activity, leading to accumulation of mitochondrial ROS, and, hence, cardiac hypertrophy. In contrast, activation of PI3KC3 improves autophagy activity, thereby reducing mitochondrial ROS and leading to a protective effect on Ang II-induced cardiac hypertrophy.